8 - Managing Religious Conflicts in Nigeria: The Inter-Religious Mediation Peace Strategy - Omotosho, Mashood (Africa Development, 2021)
Nigeria with over 150 million people consists of muslims and christians who live across the country. The religious divide in the country criss- crosses more than 250 ethnic groups as well as deep political divisions that cross religious lines. Over the last decade, numerous ‘hotspots’ around the country have suffered from pervasive violent religious conflict, with devastating impact on the citizenry and the peaceful co- existence in the Nigerian state. The February 2000 anti-Sharia crisis in Kaduna, the religious riots in 2001 and 2004 in Bauchi State, the dispute over a perceived insult to islam during a beauty pageant in 2002, the riots over Danish cartoons depicting the Prophet Mohammed in 2006, and the August 2009 Boko Haram onslaught which led to major mayhem in the Northern parts of the country are all disturbing signs of this situation. It is not surprising therefore that the Federal Government of Nigeria and some non-governmental organisations have decided to pay special attention to this challenge by putting in place innovative structures designed to provide effective solutions to the phenomenon of violent religious conflicts in Nigeria. No doubt, the inter-religious mediation organ represents an energetic and indispensable vehicle for achieving lasting peace among divergent religious groupings in the country. The questions that beg for answers therefore include: What are the salient requirements for a successful policy of inter-religious mediation strategy in terms of religious conflict management, prevention and peace building? What are the most practical alternative ways of enhancing the capacity of the inter-religious mediation group to effectively resolve religious conflict in the country? In a nutshell, the study investigates the various religious conflicts vis-à-vis the eace strategy of the ‘inter-religious mediation’ groups in the country.